Pengaruh Kepuasan dan Motivasi Kerja Terhadap Kinerja Pegawai pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Kotamobagu - Hamel, Femmy; Mawikere, Jacklyn; Endeka, Linton Roka Dexell Surya; Dwiningwarni, Sayekti Suindyah (Peneliti.net, 2026)
This study aims to analyze the relationship between job satisfaction and human resource (HR) performance at the Office of Women's Empowerment and Child Protection in Kotamobagu City. The population and sample consisted of 30 employees selected through purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability. The data were analyzed using Pearson correlation and simple linear regression to determine the strength and direction of the relationship between variables. The results indicate a positive and significant relationship between job satisfaction and HR performance. Increased employee job satisfaction positively affects performance, thereby supporting the achievement of organizational goals. This study recommends optimizing job satisfaction management to enhance employee performance in governmental institutions.